2013
DOI: 10.1080/09593330.2013.841268
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation mechanisms of pathogenic bacteria in several matrixes during the composting process in a composting toilet

Abstract: This study aimed to compare the inactivation rate and the mechanisms of pathogenic bacteria in three matrixes (sawdust, rice husk and charcoal) during the composting process. The inactivation rate was evaluated with Escherichia coli strain and the damaged parts and/or functions were evaluated with three different media. Normalized inactivation rate constant in three media and from three matrixes had no significant difference in each process (pure, 1 month and 2 months). The value in rice husk was relatively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…This TC is characterized by a mixed matter of faeces and a matrix which can be sawdust or charcoal. [11,12] TC is mainly used as a soil conditioner. However, amendment of TC slowly releases mineral fertilizers (organically bounded) and then represents a good combination with urine amendment.…”
mentioning
confidence: 99%
“…This TC is characterized by a mixed matter of faeces and a matrix which can be sawdust or charcoal. [11,12] TC is mainly used as a soil conditioner. However, amendment of TC slowly releases mineral fertilizers (organically bounded) and then represents a good combination with urine amendment.…”
mentioning
confidence: 99%
“…In that study, the sawdust had a lower pH (5.5) than the charcoal ash (12.5) (Niwagaba et al, 2009). Sossou et al (2014) suggested that rice husk charcoal ash may be a more effective desiccant in supporting fundamental microorganism inactivation mechanisms than sawdust, rice husk, and charcoal. Rice husk and sawdust are also reported to damage the outer membrane of E. coli while ash inactivates by damaging the outer membrane and/or enzyme activity and, thus, may be more lethal (Sossou et al, 2014).…”
Section: Phmentioning
confidence: 87%
“…Common desiccants are ash (from burning wood or other materials), dry soil or sand, dry leaves, dry grass, rice husks, lime (quicklime or hydrated lime), crushed oyster shells, and shea nut shells. Selection of a desiccant is typically determined by what is locally and seasonally available and is cost effective (Mehl et al, 2011;Magri et al, 2013;Sossou et al, 2014).…”
Section: Carbon Richmentioning
confidence: 99%
See 1 more Smart Citation
“…From a hygienic perspective, feces should always be considered to contain pathogens that cause gastrointestinal infections. Although the composting process in dry toilets reduces concentrations of indicator microorganisms and pathogens to some extent (Sossou et al, 2011;Sossou et al, 2014), the compost recovered from a dry toilet always has the potential to include pathogens derived from feces of infected persons, which pose infectious disease risks for users (Otaki et al, 2007). The highest infection risk most likely is posed during emptying the compost and exchanging the matrix (Nakagawa et al, 2006;Schönning et al, 2007).…”
Section: Introductionmentioning
confidence: 99%